A fast encryption method of social network privacy data based on blockchain. (4th September 2022) - Zhong, Beixin; Cheng, Shi
In order to overcome the problems of long encryption time and poor security in traditional social network privacy data encryption methods, this paper proposes a fast encryption method of social network privacy data based on block chain. Firstly, the fuzzy C-means clustering algorithm is used to cluster the privacy data in social network, so as to improve the operability of data and shorten the encryption time. Based on the clustering results, combined with the blockchain structure, the elliptic curve encryption algorithm in the blockchain is used to realise the fast encryption of social network privacy data. The experimental results show that the encryption efficiency and encryption security of the proposed method are improved effectively, and the maximum encryption security coefficient reaches 0.98.